Infectious bursal disease virus VP5 polypeptide: a phosphoinositide-binding protein required for efficient cell-to-cell virus dissemination. - Fernando Méndez; Tomás de Garay; Dolores Rodríguez; José F Rodríguez (PLoS ONE, 2015)
Infectious bursal disease virus (IBDV), a member of the Birnaviridae family, is a major avian pathogen responsible for an immunosuppressive disease affecting juvenile chickens. The IBDV genome is formed by two dsRNA segments. The largest one harbors two partially overlapping open reading frames encoding a non-structural polypeptide, known as VP5, and a large polyprotein, respectively. VP5 is non-essential for virus replication. However, it plays a major role in IBDV pathogenesis. VP5 accumulates at the plasma membrane (PM) of IBDV-infected cells. We have analyzed the mechanism underlying the VP5 PM targeting. Updated topological prediction algorithm servers fail to identify a transmembrane domain within the VP5 sequence. However, the VP5 polycationic C-terminal region, harboring three closely spaced patches formed by two or three consecutive basic amino acid residues (lysine or arginine), might account for its PM tropism. We have found that mutations, either C-terminal VP5 deletions or replacement of basic amino acids by alanine residues, that reduce the electropositive charge of the VP5 C-terminus abolish PM targeting. Lipid overlay assays performed with an affinity-purified Flag-tagged VP5 (FVP5) protein version show that this polypeptide binds several phosphoinositides (PIP), exhibiting a clear preference for monophosphate species. Experiments performed with FVP5 mutant proteins lacking the polycationic domain demonstrate that this region is essential for PIP binding. Data gathered with IBDV mutants expressing C-terminal deleted VP5 polypeptides generated by reverse genetics demonstrate that the VP5-PIP binding domain is required both for its PM targeting in infected cells, and for efficient virus dissemination. Data presented here lead us to hypothesize that IBDV might use a non-lytic VP5-dependent cell-to-cell spreading mechanism.